2021
DOI: 10.21203/rs.3.rs-715398/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sixteenth-century tomatoes in Europe: who saw them, what did they look like, and where did they come from?

Abstract: BackgroundSoon after the Spanish conquest of the Americas, the first tomatoes were presented as curiosities to the European royals and drew the attention of sixteenth-century Italian naturalists. Despite of their scientific interest in this New World crop, most Renaissance botanists did not specify where these ‘golden apples’ or ‘pomi d’oro’ came from. The debate on the first European tomatoes and their origin is often hindered by erroneous dating, botanical misidentifications and inaccessible historical sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Again: this all sounds perfectly reasonable to the art historian, but the biologist will most likely choose not to trust such pictural evidence. The biologist might instead choose to rely exclusively on botanical drawings [nicely illustrated for tomatoes by Andel et al (2021) ], found in scientific treatises on the ground that these were at least produced with the explicit intent to depict the natural world. A database of botanical drawings could be a fascinating tool, but here we are considering an even greater database, which is the whole of art.…”
mentioning
confidence: 99%
“…Again: this all sounds perfectly reasonable to the art historian, but the biologist will most likely choose not to trust such pictural evidence. The biologist might instead choose to rely exclusively on botanical drawings [nicely illustrated for tomatoes by Andel et al (2021) ], found in scientific treatises on the ground that these were at least produced with the explicit intent to depict the natural world. A database of botanical drawings could be a fascinating tool, but here we are considering an even greater database, which is the whole of art.…”
mentioning
confidence: 99%